Features of soft skills formation in the study of the discipline "Market of tourist services" - Binytska, Olena (Journal of Education, Health and Sport, 2023)
The article highlights the peculiarities of the formation of soft skills in students majoring in "Tourism" while studying the discipline "Market of tourist services". The article focuses on the key soft skills, including empathy, emotional intelligence, teamwork skills, customer service, networking and leadership, which are extremely important for the competitiveness of future tourism professionals. It is emphasized that the development of these soft skills contributes to a better adaptation of graduates to the needs of the labour market, where quality communication and customer service skills determine success in the tourism sector. The article describes that the formation of soft skills in the course of studying the discipline "Market of tourist services" involves the use of interactive methods, in particular: role-playing games and practical tasks that help students develop the necessary soft skills in real situations.